A Microscopic View of the Store-Operated Calcium Entry-Pathway. (10th November 2013) - Pacheco, Jonathan; Vaca, Luis
Abstract : Orai and STIM are the basic components of a highly complex and regulated mechanism for Ca 2+ entry into the cell, known as store-operated calcium entry (SOCE). The activation of plasma membrane G-protein-coupled receptors associated with the phospholipase C cascade results in the rapid and massive production of inositol 1, 4, 5-triphosphate (IP3 ). This second messenger triggers the massive efflux of Ca 2+ from the endoplasmic reticulum and into the cytosol, resulting in the oligomerization of the stromal interacting molecule (STIM1), a sensor of ER Ca 2+ . STIM1 oligomers (the so-called puncta) activate Orai channels at the plasma membrane, triggering the influx of Ca 2+ into the cytosol. Several microscopy techniques have been implemented to study SOCE, resulting in stunning images of protein complexes assembling in real time. However, little attention has been paid to the findings about this complex mechanism from the imaging point of view, some of which appear to produce contradictory results. In the present review we gathered all the information about SOCE obtained with imaging techniques and contrast these findings with those obtained with alternative methods.